PENGEMBANGAN MEDIA BOOKLET UNTUK MENINGKATKAN EFIKASI DIRI PADA SISWA - Khoerunnisa; Samsudin, Asep; Oktasari, Resti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
During the learning process, students often lack confidence when working on tasks. The solution is to use group guidance with booklet media. This research aims to develop, test, and identify constraints in using booklet media. The Research and Development method is employed, with the research population consisting of students from SMP Negeri 2 Cipanas. The results indicate that the development of self-efficacy booklet media follows the established steps. The feasibility test shows a positive outcome with a feasibility rate of 86.08%. The use of booklet media successfully enhances students' self-efficacy. Constraints encountered include limited resources, student conditions, and limited service time. Overall, this research successfully develops self-efficacy booklet media for group guidance.